PERANCANGAN SISTEM INFORMASI ABSENSI SEKOLAH BERBASIS WEB DI SMP PGRI 35 SERPONG - Ahya Mahfuzi; Nailah Rahadatul ‘Aisy; Ahmad Faisal; Wasis Haryono (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
One of the important components that support the teaching and learning process teaching and learning in schools is student participation. Some of the challenges often faced by manual attendance systems that are still in use include inefficient recording inefficient recording, the risk of data loss, and the difficulty of managing the attendance recapitulation. The purpose of this research is to create a school attendance information system information system that can be accessed via the internet at SMP PGRI 35 Serpong. Attendance recording, student data management, and digital attendance report recapitulation are all the objectives of the system. report recapitulation are all objectives of this system. Needs analysis,system design, implementation, testing, and maintenance are the stages of the waterfall method used in the development of this system.stages of the waterfall method used in system development. This system uses technologies such as Laravel framework version 8, MySQL database, and web hosting to ensure the online accessibility of the system.web hosting to ensure the accessibility of the system online. One of the features main features of the system are recording teacher attendance, managing lesson schedules, recapitulation of attendance data by principals and homeroom teachers, and administrator access to manage school data.administrator access to manage school data. The test results show that this system can improve the attendance process at SMP PGRI 35 Serpong and more efficient. efficient. This system makes the attendance management process more organized, clear, and easily accessible by interested parties.